Trends in public perceptions of patient safety during the COVID-19 pandemic: Findings from a repeated cross-sectional survey in Germany, 2019–2023 - Olga Amberger; Dorothea Lemke; Hardy Müller; David Schwappach; Max Geraedts; Beate S. Müller (PLoS ONE, 2025)
In recent years, public perceptions of patient safety have evolved significantly, driven by media coverage, healthcare reforms, and greater awareness during the coronavirus disease 2019 (COVID-19) pandemic. The present study aimed to examine trends in public perceptions of patient safety, knowledge and self-efficacy in Germany during this pandemic between 2019 and 2023. A repeated cross-sectional study was conducted, using data from TK Monitor of Patient Safety. TK Monitor of Patient Safety in a nationwide survey assessing public perceptions of safety in medical treatment and diagnosis. Self-reported data were collected annually from a randomly selected sample of 1,000 different adults aged 18 and older residing in Germany. Statistical analyses included descriptive statistics, chi-square tests, and linear regressions for trend analyses. Our results revealed high perceived patient safety risk during the years of the study. Up to one third of respondents considered it very likely or somewhat likely that patients would be harmed when receiving medical treatment in hospital or ambulatory care, with lower perceived levels of risk before the COVID-19 pandemic. Regarding perceived prevalence of preventable adverse events, over half of respondents considered it very likely or somewhat likely that an illness of theirs would be diagnosed incorrectly, or that they would contract a nosocomial infection, at some stage in their lives. The majority of respondents considered themselves overall well informed about patient safety and reported higher levels of self-efficacy with regard to error prevention before and after the pandemic than during it. Given the facts that patient safety remains an important issue and that the German public perceives the level of patient safety risk but also of patient safety knowledge, and self-efficacy as high, actively involving patients in safety initiatives is essential for shaping positive public perception.